Perancangan Dan Implementasi E-Commerce Pada Jasa Titipan Luar Negeri (Cargo) Studi Kasus JNE Cabang Rantauprapat - Rangkuti, M. Andri Gautama; Yanris, Gomal Juni; Sihombing, Volvo (Journal of Computer Science and Information System(JCoInS), 2025)
The development of information technology has driven transformation in various sectors, including international logistics services that demand speed, accuracy, and transparency of information. JNE Rantauprapat Branch, as a provider of international courier services, requires an integrated e-commerce system to address the challenges of services that were previously manual. This study uses the Waterfall method with structured stages of needs analysis, system design, implementation, testing, and maintenance. The technologies used include Laravel and MySQL, with testing conducted through black-box testing and user acceptance testing. The results show that the developed e-commerce system successfully integrates online ordering, shipping cost checking, real-time tracking, and international outlet tracking features effectively. This system is able to provide accurate information, reduce staff workload, and increase customer satisfaction. The research discussion confirms that this digital transformation not only simplifies operational processes but also strengthens the branch's competitiveness in the international logistics market. In addition, this system opens up opportunities for optimizing data management to support strategic decision-making. In conclusion, the implementation of e-commerce in international cargo services at JNE Rantauprapat Branch has been proven to improve efficiency and service quality. This implementation is also a long-term strategy to maintain competitiveness in the increasingly competitive digital era.